Computer-based lesson planning for the subject of Islamic Culture History - Guntur Cahyono (ATTARBIYAH: Journal of Islamic Culture and Education, 2017)
AbstractThis study aims to describe the planning, implementation, evaluation, constraints and advantages of computer utilization in the History of Islamic Culture subject in MAN Salatiga. This research is a field study, aimed at studying intensively the background, current state, and environmental interaction of a social unit. Viewed from the type of data collected, this research is included in the category of qualitative research. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from the people, or their behavior that can be observed. Subjects of this study are teachers and students. Data collection techniques used are observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and conclusions. The results of this study indicate that the planning is done by classroom teachers by making lesson plan based on 2013 Curriculum guideline. Teachers have written the utilization of computers on the lesson plan components. Utilization of computers in the classroom is as a medium and the one in the computer laboratory as media and learning resources. Computers are used as a substitute for books due to their limited availability. It is also practiced as a habituation for preparing the computer-based national examination (UNBK). Keywords: computer utilization, learning, history of Islamic culture subject Abstrak Penelitian ini bertujuan untuk mendeskripsikan perencanaan, pelaksanaan, evaluasi, kendala dan kelebihan pemanfaatan komputer dalam pembelajaran mata pelajaran Sejarah Kebudayaan Islam di MAN Salatiga. Penelitian ini merupakan penelitian lapangan bertujuan mempelajari secara intensif latar belakang, keadaan sekarang, dan interaksi lingkungan suatu unit sosial. Jika dilihat dari jenis data yang dikumpulkan, maka penelitian ini termasuk dalam kategori penelitian kualitatif. Penelitian kualitatif sebagai prosedur penelitian yang menghasilkan data deskriptif berupa kata-kata tertulis atau lisan dari orang-orang atau perilaku yang dapat diamati Subjek penelitian ini adalah guru dan siswa. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Analisis data menggunakan langkah-langkah reduksi data, penyajian data, dan penarikan kesimpulan.  Hasil penelitian ini menunjukkan bahwa perencanaan dilakukan oleh guru kelas dengan membuat RPP menggunakan pedoman Kurikulum 2013. Guru sudah menuliskan pemanfaatan komputer pada komponen RPP. Pemanfaatan komputer di kelas sebagai media dan di laboratorium komputer sebagai media dan sumber belajar. Komputer dijadikan sebagai alat pengganti buku karena terbatasnya ketersediaan buku. Sekaligus sebagai pembiasaan komputer untuk persiapan UNBK.                                                                                                          Kata kunci: pemanfaatan komputer, pembelajaran, SKI